2013
DOI: 10.1101/gad.215459.113
|View full text |Cite
|
Sign up to set email alerts
|

Extensive polymerase pausing during Drosophila axis patterning enables high-level and pliable transcription

Abstract: Cascades of zygotic gene expression pattern the anterior-posterior (AP) and dorsal-ventral (DV) axes of the early Drosophila embryo. Here, we used the global run-on sequencing assay (GRO-seq) to map the genome-wide RNA polymerase distribution during early Drosophila embryogenesis, thus providing insights into how genes are regulated. We identify widespread promoter-proximal pausing yet show that the presence of paused polymerase does not necessarily equate to direct regulation through pause release to producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 62 publications
9
86
0
2
Order By: Relevance
“…However, it has been observed that patterns of Pol II density on promoters and gene bodies change in response to heat shock, hormones, and developmental signals 10,29,4650 , indicating that the two prominent regulatory steps during early elongation are Pol II recruitment to the promoter and the release of paused Pol II to productive elongation (FIG. 1b).…”
Section: Mechanisms That Contribute To Pausingmentioning
confidence: 99%
“…However, it has been observed that patterns of Pol II density on promoters and gene bodies change in response to heat shock, hormones, and developmental signals 10,29,4650 , indicating that the two prominent regulatory steps during early elongation are Pol II recruitment to the promoter and the release of paused Pol II to productive elongation (FIG. 1b).…”
Section: Mechanisms That Contribute To Pausingmentioning
confidence: 99%
“…In Drosophila , widespread Pol II pausing is first detected at the midblastula transition (MBT) stage [36]. GRO-seq assays have further revealed that ~55% of genes in early Drosophila embryos contain paused Pol II, and that pause release appears to be the dominant regulatory step for genes involved in anterior–posterior and dorsal-ventral axis patterning [75]. Using muscle development in Drosophila embryos as a model, Gaertner et al have shown that at different embryonic stages, a large number of inactive genes gradually acquire paused Pol II during the developmental time course and are poised for future gene activation by tissue-specific signals [37].…”
Section: Pause Release Signalsmentioning
confidence: 99%
“…Activation of Sxl Pe is biphasic; the promoter is first set up in repressive chromatin which is the default or male state, after which it transitions to activation in females [24, 42]. The R1 region and R2 sense lncRNAs appear to favor this repressed state.…”
Section: Discussionmentioning
confidence: 99%